A Cross-Sector Agro-Marine Innovation Management Model for Integrated Sustainability - Yasintha Wahida Tiana; Wanda Khairun Nasirin; Wanda Ramadhana; Jasella Sakwi Yanti; Nurmah Fudzah (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2026)
Contemporary natural resource-based economies, particularly agriculture and marine sectors, are increasingly challenged to reconcile productivity growth with environmental sustainability and systemic resilience. However, existing literature continues to conceptualize green and blue domains in isolation, revealing a persistent gap in the development of an integrated agro-marine innovation framework. This study addresses this gap by developing a cross-sector conceptual model that integrates agro and marine innovation within a sustainability-oriented systems perspective. A qualitative grounded theory approach is employed based on systematic analysis of 583 Scopus-indexed publications. Data were analyzed through open, axial, and selective coding using NVivo to construct an inductive conceptual model. Findings indicate that innovation operates as an interconnected system comprising four causal layers, namely drivers, mechanisms, outputs, and outcomes. Technological innovation, institutional arrangements, financial mechanisms, and multi-actor collaboration emerge as interdependent drivers shaping agro-marine transformation through production system reconfiguration, business model innovation, and value chain restructuring. These mechanisms enhance efficiency and economic performance, facilitating broader transitions toward sustainability, resilience, and inclusive development. From a policy perspective, the model highlights the need for integrated governance structures, coherent green-blue financing systems, and coordinated transformation strategies. From a societal perspective, it suggests improvements in livelihood quality, spatial equity, and food system resilience. The originality of this study lies in proposing the Integrated Sustainable Agro-Marine Innovation System as a novel conceptual model derived from Scopus-based grounded theory synthesis, offering a unified systemic framework that integrates green and blue economy paradigms within a single analytical structure for sustainability transitions.